2012
DOI: 10.2174/1874120701206010073
|View full text |Cite
|
Sign up to set email alerts
|

PEEK (Polyether-ether-ketone) Based Cervical Total Disc Arthroplasty: Contact Stress and Lubrication Analysis

Abstract: This paper presents a theoretical analysis of the maximum contact stress and the lubrication regimes for PEEK (Polyether-ether-ketone) based self-mating cervical total disc arthroplasty. The NuNec ® cervical disc arthroplasty system was chosen as the study object, which was then analytically modelled as a ball on socket joint. A non-adhesion Hertzian contact model and elastohydrodynamic lubrication theory were used to predict the maximum contact stress and the minimum film thickness, respectively. The peak con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…As listed in Table 3 , the initial surface roughness of FDM printed PEEK parts were in sub-micro level ( Ra from 0.613 to 0.667 μm) and met the basic surface quality requirement of polymeric prothesis. For NuNec ® PEEK self-mating disc prothesis prepared by injection molding and machining, its surface roughness was documented as Ra ≤ 0.585 μm [ 31 ]. After polishing treatment, Ra can be further reduced to the range of 0.106 to 0.155 μm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As listed in Table 3 , the initial surface roughness of FDM printed PEEK parts were in sub-micro level ( Ra from 0.613 to 0.667 μm) and met the basic surface quality requirement of polymeric prothesis. For NuNec ® PEEK self-mating disc prothesis prepared by injection molding and machining, its surface roughness was documented as Ra ≤ 0.585 μm [ 31 ]. After polishing treatment, Ra can be further reduced to the range of 0.106 to 0.155 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Surface roughness was measured using a contact typed roughness measuring device (Mar Surf M 300C, Mahr GmbH, Göttingen, Germany) with a 2 μm radius diamond stylus and an examining area of 4 × 4 mm 2 . A Gaussian filter (cut-off length 0.8 mm) was used to separate roughness from waviness [ 31 ]. Special attention should be paid to avoid the scratching of the surface when using the contact typed roughness measuring device.…”
Section: Experiential Methodsmentioning
confidence: 99%
“…A previous theoretical analysis of PEEK based cervical disc shows that NuNec s cervical disc will operate with a boundary lubrication, under natural cervical spine operating conditions [29].…”
Section: Discussionmentioning
confidence: 96%
“…Fatigue wear mainly depends on the contact stress and the bearing material, which in turn depend on the prosthesis design [27]. A previous contact stress analysis showed that the maximum Hertzian contact stress of NuNec s cervical disc replacement of the smallest size is 32.1 MPa [29]. The experienced contact stresses between the bearing surfaces of other comparable studies were unknown [25,32], due to lack of information of the bearing design (ball radius and radial clearance).…”
Section: Discussionmentioning
confidence: 99%
“…Contact type between cylindrical roller and spiral groove can be equivalent to the two cylinders' line contact. According to Hertz contact theory, the maximum contact stress between the two is the formula [13]:…”
Section: Contact Analysis Of the Screw Pairmentioning
confidence: 99%